Event-related potentials during literacy acquisition - Rebreikina, A.B.; Larionova, E.V.; Martynova, O.V. (Sovremennaâ Zarubežnaâ Psihologiâ, 2020)
Literacy is a complex and multidimensional phenomenon that has been well studied in psychology and pedagogy. Neurophysiologists try to understand the mechanisms of writing and reading acquisition by analyzing different linguistic processes. In this paper, we review the data that were revealed by using the event-related potentials (ERPs) method in the light of spelling, lexical, semantic and syntactic aspects of literacy, as well as changes in the components of ERPs in children and adults during language acquisition and in dyslexia, the most studied reading disorder. The ERPs method can help to understand both the general, universal neural underpinnings of literacy development and the unique features of different languages. Грамотность – сложное разноплановое явление, хорошо изученное в психологии и педагогике. Анализируя отдельные лингвистические процессы, нейрофизиологи пытаются понять механизмы овладения письмом и чтением. В настоящей работе мы рассматриваем данные, полученные с помощью метода вызванных потенциалов, в свете орфографических, лексических, семантических, синтаксических аспектов грамотности, а также изменения компонентов вызванных потенциалов у детей и взрослых в процессе освоения языка и при дислексии – наиболее изученном нарушении чтения. Метод вызванных потенциалов может помочь понять как общие, универсальные нейрофизиологические основы развития грамотности, так и уникальные особенности разных языков.